Titania-carbon nanotubes nanocomposite coating on Mg alloy: microstructural characterisation and mechanical properties. Issue 4 (4th March 2018) - Bakhsheshi-Rad, H. R.; Hamzah, E.; Ismail, A. F.; Aziz, M.; Daroonparvar, M.; Parham, S.; Hadisi, Z.; Yajid, M. A. M.
ABSTRACT: Atmospheric plasma spraying was carried out to deposit a bilayered NiCrAlY/nTiO2 -CNT composite coating. Initially, NiCrAlY, as an under-layer with a thickness of around 100 µm, was deposited. Afterwards, nanostructured TiO2 (nTiO2 ), as an over-layer with a thickness of 135 μm, was deposited with and without the incorporation of carbon nanotubes (CNTs) on the Mg alloy surface. In contrast to NiCrAlY and NiCrAlY/nTiO2, the NiCrAlY/nTiO2 -CNT nanocomposite coating displayed a higher bonding strength. The wear behaviour of the coatings was examined by the pin-on-disc test and the results revealed that the incorporation of CNTs into the nTiO2 coating considerably enhanced the tribological behaviour of Mg alloy due to the CNT's bridging mechanism.